High Densities of Large Herbivores Rapidly Disrupt Ecosystem Integrity - Jorge Isla; Emmanuel Serrano; Juan A. Calleja; Carlos Hernández‐Castellano; Rafael Alcalá‐Herrera; Elena Albanell; Carlos Alonso; Elena Baraza; Matthew Brolly; Niall Burnside; Ana Burón‐Ugarte; Miquel Capó; et al. (Global Change Biology, 2026)
Human‐induced high densities of large wild herbivores may pose a threat to natural ecosystems, modifying biodiversity and ecosystem functioning. Although the negative impacts on individual taxa and processes are well documented, a comprehensive understanding of how ecosystem integrity responds to high herbivore densities remains limited. This study addresses this gap through an extensive herbivore‐density manipulation experiment conducted in two Mediterranean woodlands. We established two scenarios of high red deer ( Cervus elaphus ) density, representative of some protected areas (~30 individuals·km 2 ) and intensively managed hunting estates (~90 individuals·km 2 ). We monitored 38 metrics encompassing a broad spectrum of biodiversity and functional responses to synthesize the short‐term impacts of high herbivore densities. We revealed an overall 13% decline in ecosystem integrity after one year of exposure to high herbivore densities, with particularly widespread impacts on functional responses and detrimental effects on biodiversity components. We detected rapid declines in plant diversity and a positive response of epigeic invertebrate orders. Conversely, ants (analyzed separately), birds, and small mammals remained mostly unaffected. Functional responses were consistently impaired, including declines in plant regeneration and physiological performance, simplified pollination networks, degraded soil structure, and increased disease vectors. These findings show that human‐induced high herbivore densities rapidly create conditions that disrupt ecosystem integrity, reveal early signs of ecological degradation, and underscore the urgent need for population regulation.

Ungulate: vehicle collision rates are associated with the phase of the moon - Victor J. Colino-Rabanal; Tom A. Langen; Salvador J. Peris; Miguel Lizana (Biodiversity and Conservation, 2018)

Factors influencing wolf Canis lupus roadkills in Northwest Spain - Victor Javier Colino-Rabanal; Miguel Lizana; Salvador J. Peris (European Journal of Wildlife Research, 2011)